Primary Prophylaxis With Biosimilar Filgrastim for Patients at Intermediate Risk for Febrile Neutropenia: A Cost-Effectiveness Analysis. Issue 8 (August 2021) - Li, Edward; Mezzio, Dylan J.; Campbell, David; Campbell, Kim; Lyman, Gary H.
Abstract : PURPOSE: Temporary COVID-19 guideline recommendations have recently been issued to expand the use of colony-stimulating factors in patients with cancer with intermediate to high risk for febrile neutropenia (FN). We evaluated the cost-effectiveness of primary prophylaxis (PP) with biosimilar filgrastim-sndz in patients with intermediate risk of FN compared with secondary prophylaxis (SP) over three different cancer types. METHODS: A Markov decision analytic model was constructed from the US payer perspective over a lifetime horizon to evaluate PP versus SP in patients with breast cancer, non–small-cell lung cancer (NSCLC), and non-Hodgkin lymphoma (NHL). Cost-effectiveness was evaluated over a range of willingness-to-pay thresholds for incremental cost per FN avoided, life year gained, and quality-adjusted life year (QALY) gained. Sensitivity analyses evaluated uncertainty. RESULTS: Compared with SP, PP provided an additional 0.102-0.144 LYs and 0.065-0.130 QALYs. The incremental cost-effectiveness ranged from $5, 660 in US dollars (USD) to $20, 806 USD per FN event avoided, $5, 123 to $31, 077 USD per life year gained, and $7, 213 to $35, 563 USD per QALY gained. Over 1, 000 iterations, there were 73.6%, 99.4%, and 91.8% probabilities that PP was cost-effective at a willingness to pay of $50, 000 USD per QALY gained for breast cancer, NSCLC, and NHL, respectively. CONCLUSION: PP with a biosimilar filgrastim (specifically filgrastim-sndz) is cost-effective in patients with intermediate risk for FN receiving curative chemotherapy regimens for breast cancer, NSCLC, and NHL. Expanding the use of colony-stimulating factors for patients may be valuable in reducing unnecessary health care visits for patients with cancer at risk of complications because of COVID-19 and should be considered for the indefinite future.